Improving Service Quality Through Customer Satisfaction of Type D Hospital : A Phenomenological Approach - Ayu Pratiwi; Saophasith Channgakham; Myat Thinzar Lin (Ilomata International Journal of Social Science, 2023)
Health is very important for all humans because without good health, every human being will find it difficult to carry out their daily activities. Hospitals as one of the health care facilities in general have a very important role in efforts to improve the health status of the Indonesian people. However, until now, there are still many complaints from the public regarding the services obtained from the hospital. This study aims to answer the question of how the quality of service in a type D hospital is, and how is patient satisfaction in this type of hospital. This study uses a phenomenological approach to explore customer’s experience after being a patient in a type D hospital for 2 years. Data collection was carried out by means of in-depth unstructured interviews, in a very fluid atmosphere where the informants could tell their experiences freely. The results showed that the five aspects of service quality, namely tangibles, reliability, responsiveness, assurance and empathy, played a very important role in determining patient satisfaction in type D hospitals.